(untitled) (Veterinary Science, 2017)
The antispasmodic activity attributed by the popular medicine in methanolic extracts of Sida rhombifolia (n.v. afata), Bacchar is articulate, Chenopodium ambrosioides (n.v.paico macho) and Conyza bonariensis (n.v. rama negra) collected in La Pampa, Argentina was verified. The essays consisted m take seried contrast radiography of mice previously administered with the extracts. The antispasmodic activities was evaluated observing the comparative progress of the radio-opaque gastrointestinal tract in animals treated with the extracts in relation to atropin treated animals and the control group. The effect of the extracts on the transit gastrointestinal was estimated determining the time in which the evacuation of the substance radio-opaque begins and the time of gastric emptying.substance through the We conclude that the extracts of Sida rhombifolia, Baccharis articulata, Chenopodium ambrosioides and Conyza bonariensis which develop in La Pampa exhibit antispasmodic effects. The different effects found on the time of gastric ernptying and the intestinal transit suggests different mechanisms and places of action